Advances in Miniaturized Computational Spectrometers - Xue, Qian; Yang, Yang; Ma, Wenkai; Zhang, Hanqiu; Zhang, Daoli; Lan, Xinzheng; Gao, Liang; Zhang, Jianbing; Tang, Jiang (Advanced science, 2024)
Miniaturized computational spectrometers have emerged as a promising strategy for miniaturized spectrometers, which breaks the compromise between footprint and performance in traditional miniaturized spectrometers by introducing computational resources. They have attracted widespread attention and a variety of materials, optical structures, and photodetectors are adopted to fabricate computational spectrometers with the cooperation of reconstruction algorithms. Here, a comprehensive review of miniaturized computational spectrometers, focusing on two crucial components: spectral encoding and reconstruction algorithms are provided. Principles, features, and recent progress of spectral encoding strategies are summarized in detail, including space‐modulated, time‐modulated, and light‐source spectral encoding. The reconstruction algorithms are classified into traditional and deep learning algorithms, and they are carefully analyzed based on the mathematical models required for spectral reconstruction. Drawing from the analysis of the two components, cooperations between them are considered, figures of merits for miniaturized computational spectrometers are highlighted, optimization strategies for improving their performance are outlined, and considerations in operating these systems are provided. The application of miniaturized computational spectrometers to achieve hyperspectral imaging is also discussed. Finally, the insights into the potential future applications and developments of computational spectrometers are provided. This review presents a comprehensive overview of miniaturized computational spectrometers, focusing on spectral encoding strategies and reconstruction algorithms. The analysis includes recent advances, optimization strategies, performance metrics, and considerations for practical applications. Additionally, the application of these spectrometers for hyperspectral imaging and insights into future developments are discussed, highlighting their potential for various fields.